Significance of eosinophilia in granulomatosis with polyangiitis: data from the French Vasculitis Study Group Registry. (17th June 2021) - Iudici, Michele; Puéchal, Xavier; Pagnoux, Christian; Courvoisier, Delphine S; Hamidou, Mohamed; Blanchard-Delaunay, Claire; Maurier, François; Ruivard, Marc; Quéméneur, Thomas; Aumaître, Olivier; Guillevin, Loïc; Terrier, Benjamin; et al.
Abstract: Objective: To describe disease presentation and long-term outcome of granulomatosis with polyangiitis (GPA) patients according to blood eosinophils count (Eos) at vasculitis diagnosis. Methods: Data from newly diagnosed GPA patients registered in the French Vasculitis Study Group database with available eosinophil count at diagnosis were reviewed. Disease characteristics, rate and type of relapses, and overall survival were analysed according to Eos, categorized as normal (<500/mm 3 ), mild-to-moderate hypereosinophilia (HE) (between 500 and 1500/mm 3 ) and severe HE (>1500/mm 3 ). Results: Three hundred and fifty-four patients were included. At diagnosis, 90 (25.4%) patients had HE ≥500/mm 3 ; they were more likely male (73% vs 56%, P = 0.006) and had more frequent cutaneous manifestations (49% vs 33%, P = 0.01), peripheral neuropathy (32% vs 17%, P = 0.004) and higher BVAS (21 vs 18, P = 0.01), compared with those with Eos <500/mm 3 . Patients with severe HE ( n = 28; median Eos 2355, range 1500–9114) had more frequent renal function worsening at presentation ( P = 0.008). After a median follow-up of 3.95 (interquartile range 1.95–6.76) years, no difference was found in overall relapse rates according to baseline Eos, but those with HE experienced more neurological ( P = 0.013) and skin ( P = 0.024) relapses and had more frequently peripheral neuropathy as damage at last follow-up ( P = 0.02). Overall survival was not significantly different in patients with normal Eos or HE at diagnosis. ( P = 0.08). Conclusions: Blood HE at diagnosis, observed in about one-quarter of GPA patients, identifies a subgroup of patients with a more severe disease and higher rate of skin and neurological involvement both at presentation and during follow-up.